Deradikalisasi Badan Nasional Penanggulangan Terorisme (BNPT) pada Teroris Wanita dalam Upaya Pertahanan Negara Terhadap Terorisme - Amelia Widya Octa Kuncoro Putri; Pujo Widodo; Suhirwan Suhirwan (Jurnal Community, 2022)
Women's relationship with terrorism has undergone a considerable paradigm shift. This is because women who were originally associated as victims of terrorism, are now transformed into diverse roles as facilitators, recruiters, nurses, couriers, suicide perpetrators, to militants on the front lines of terrorism. In this paper the method used is a qualitative method with literature study techniques. Qualitative methods is used to be able to describe research topics more explorative. The involvement of women in acts of terror in Indonesia was first identified in 2004 where Detachment 88 captured Munifatun, the wife of terrorist Noordin M. Top. Furthermore, women who are perpetrators of terror that are quite attention-grabbing occurred throughout 2021. When viewed more broadly, in terms of numbers, men still dominate. But the number of women arrested in terrorism cases increased significantly from four cases in 2011-2015 to thirty-two cases in 2016-2020. BNPT has placed women as special objects in the deradicalization program, as the role of women in terrorism changes. BNPT does this not as a form of gender bias, but as a difference in the deradicalization approach between men and women.